Retention of provisional crowns cemented with eight temporary cements: comparative study Retenção de coroas provisórias cimentadas com oito cimentos temporários: estudo comparativo - Mariana Ribeiro de Moraes Rego; Luiz Carlos Santiago (University of São Paulo, 2004)
Many temporary cements are commercially available; therefore, it is necessary to indicate them for each clinical requirement with regard to the tensile strength of prosthetic retainers. Thus, the purpose of this study was to compare the retention of provisional crowns cemented with eight temporary cements, over full crown preparations with standardized mechanical principles as height, taper, and length. For that purpose, eighty human first premolars received full crown preparation with standardized height and taper. Provisional crowns were fabricated and luted with eight brands of temporary cements. Twenty four hours after cementation, the restorations were submitted to tensile strength test in a universal testing machine and the data submitted to ANOVA and Bonferroni tests. Mean tensile strength values ranged from 20.1N for Nogenol cement to 67.5N for Hydro C cement. Statistically significant difference (p<0.05) was found between Hydro C and the other groups, except for Temp Bond and Rely X Temp, which presented statistically significant difference when compared to Freegenol and Nogenol temporary cements. The crowns cemented with Hydro C cement were more retentive that than those cemented with the other cements, except for Rely X Temp and Temp Bond. The less retentive crowns were those cemented with Nogenol and Freegenol temporary cements. Muitas marcas de cimentos temporários estão disponíveis no mercado odontológico, sendo necessário adequá-los a cada necessidade clínica no que diz respeito à resistência à remoção dos retentores protéticos. Assim, o objetivo desse estudo foi avaliar a retenção de coroas provisórias cimentadas com oito cimentos temporários sobre preparos para coroa total com princípios mecânicos padrozinados como altura, conicidade e extensão. Para isso, oitenta primeiros pré-molares humanos receberam preparos para coroa total com altura e conicidade padronizadas. Coroas provisórias foram confeccionadas e cimentadas com oito marcas de cimentos temporários. Vinte e quatro horas após a cimentação, as restaurações foram tracionadas em uma máquina universal de ensaios e os dados submetidos aos testes estatísticos de ANOVA e Bonferroni. Os valores médios de resistência à tração variaram de 20,1 para o Nogenol a 67,5 para o Hydro C. Diferença estatisticamente significante (p<0.05) foi encontrada entre o cimento Hydro C e os outros grupos, com exceção do Rely X Temp e do Temp Bond, que apresentaram diferença estatisticamente significante quando comparados aos cimentos Freegenol e Nogenol. As coroas cimentadas com Hydro C foram mais retentivas do que aquelas cimentadas com os outros cimentos com exceção do Rely X Temp e do Temp Bond. As coroas menos retentivas foram aquelas cimentadas com os cimentos Nogenol e Freegenol.